ANALISIS PENGARUH RASIO – RASIO RISK BASED BANK RATING TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI - Yani Suryani; Azwansyah Habibie (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2017)
The purpose of this research is to analyze the influence of the Non Performing Loan, Good Corporate Governance, Return On Asset and Capital Adequacy Ratio of Earnings Growth Banking firm listed on Indonesia Stock Exchange during 2012 - 2015. The Using of analyzing method is by multiple regression analysis. For examine of the independent variable to dependent variable partially and simultaneously with significant alpha 5%. The Result of this study show that Non Performing Loan, Good Corporate Governance, Return On Asset and Capital Adequacy Ratio influence Earnings Growth simultaneously. But Only Return On Asset that influence profitability partially significant. Non Performing Loan, Good Corporate Governance and  Capital Adequacy Ratio do not influence profitability significantly.